2023
DOI: 10.7759/cureus.35700
|View full text |Cite
|
Sign up to set email alerts
|

Short Stature: Think About the Pituitary Stalk Interruption Syndrome

Abstract: Pituitary stalk interruption syndrome (PSIS) is an uncommon congenital defect of the pituitary gland. It is considered one of the rare endocrinal causes of abnormally short stature. Herein, we present a case of a four-year-old girl who consulted for short stature and delayed growth. The patient's history did not include any past medical or surgical pathology. Birth history revealed a full-term delivery with a breech presentation. Clinically, the patient had a small stature, beneath the third percentile. Magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The suggested mechanism for pituitary stalk interruption syndrome can involve genetic mutations in various genes, such as LHX3/LHX4, PIT1, PROP1, TGIF, PROKR2, OTX2, GPR161, HESX1, and ROBO1, which are linked to the development of the anterior pituitary gland [3,6]. Additionally, some studies have suggested that Breech delivery, cesarean section, and neonatal hypoxemia may result in damage to the pituitary gland [5,7]. The parents of the existing case reported no complications during breech delivery and neonatal stage, and unfortunately, no genetic testing was performed for the case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suggested mechanism for pituitary stalk interruption syndrome can involve genetic mutations in various genes, such as LHX3/LHX4, PIT1, PROP1, TGIF, PROKR2, OTX2, GPR161, HESX1, and ROBO1, which are linked to the development of the anterior pituitary gland [3,6]. Additionally, some studies have suggested that Breech delivery, cesarean section, and neonatal hypoxemia may result in damage to the pituitary gland [5,7]. The parents of the existing case reported no complications during breech delivery and neonatal stage, and unfortunately, no genetic testing was performed for the case.…”
Section: Discussionmentioning
confidence: 99%
“…PSIS has a significant impact on patient health and quality of life. The underlying causes and mechanisms of this condition remain poorly understood, yet, it is thought to be a result of a complex interplay of genetic mutations and environmental factors [5,6].…”
Section: Introductionmentioning
confidence: 99%